Sybase performance tunning - Roy, Shaibal (Prentice Hall PTR, 1996)
Sybase is the seventh largest software company in the world and a part of the fastest growing segment of the computer software industry (database technology). This book offers a detailed look at Sybase SQL Server Performance Tuning and a sneak peek at Sybase System 11 performance features. Includes a glossary of common performance tools and techniques.